Analisis Electronic Service Quality pada Aplikasi Gojek (Studi pada Masyarakat Kota Garut) - Alkadri, Mohamad Habib; Mukaram (Applied Business and Administration Journal, 2022)
Gojek is the pioneer of transportation in the first network in Indonesia which has been operating since 2010. The various online transportation services provided by Gojek are very diverse. The variety of services offered by Gojek makes the Gojek application have a lot of electronic services in it. The response of application users is not always positive with the existing electronic services in the Gojek application, but there is the possibility of a negative response given by users to the Gojek application. This phenomenon became the focus of research to determine the Quality of Electronic Services on the Gojek Application, by taking a study of the people of Garut City. In this study using quantitative descriptive analysis method, with the basis of the analysis is the calculation of the mean (average), standard deviation, maximum and minimum values. Respondents are Gojek application users in Garut City. Collecting data using an online questionnaire, namely Google Form with 104 respondents. The results of this study conclude that the quality of electronic services on the Gojek application is included in the Good criteria. The dimension that gets the highest score is the Efficiency dimension, while the dimension that gets the lowest score is Compensation.